Impact of a social network-based intervention promoting diabetes self-management in socioeconomically deprived patients: a qualitative evaluation of the intervention strategies - Vissenberg, C (BMJ Open, 2016)
OBJECTIVE: There is a need for effective interventions that improve diabetes self-management (DSM) among socioeconomically deprived patients with type 2 diabetes. The group-based intervention Powerful Together with Diabetes (PTWD) aimed to increase social support for DSM and decrease social influences hindering DSM (eg, peer pressure, social norms) in patients living in deprived neighbourhoods. Through a qualitative process evaluation, this paper aims to study whether this intervention changed social support and social influences, and which elements of the intervention contributed to this. METHODS: The intervention group (IG) was compared with a standard group-based educational intervention (control group, CG). 27 qualitative in-depth interviews with participants (multiethnic sample) and 24 interviews with group leaders were conducted. Interviews were coded and analysed using MAXQDA according to framework analysis. RESULTS: Patients in the IG experienced more emotional support from group members and more instrumental and appraisal support from relatives than those in the CG. Also, they were better able to recognise and cope with influences that hinder their DSM, exhibited more positive norms towards DSM and increased their priority regarding DSM and their adherence. Finally, the engagement in DSM by relatives of participants increased. Creating trust between group members, skills training, practising together and actively involving relatives through action plans contributed to these changes. CONCLUSIONS: A group-based intervention aimed at creating trust, practising together and involving relatives has the potential to increase social support and diminish social influences hindering DSM in socioeconomically deprived patients with diabetes. Promising elements of the intervention were skills training and providing feedback using role-playing exercises in group sessions with patients, as well as the involvement of patients' significant others in self-management tasks, and actively involving them in making an action plan for self-management. These positive results justify the value of further evaluating the effectiveness of this intervention in a larger sample. TRIAL REGISTRATION NUMBER: NTR1886, Results.